TO THE QUESTION OF DIAGNOSTICS AND PATHOGENETIC THERAPY OF ENTEROPATHY IN PATIENTS WITH CHOLELITHIASIS - Ya. M. Vakhrushev; A. P. Lukashevich (SINAPS LLC, 2016)
The aim. Specification the features of violations of the functional characteristics of the small intestine and definition the way of correction in patients with cholelithiasis. Materials and methods. 75 patients with prestone stage of cholelithiasis were examined. Clinical symptoms, cavitary, membrane digestion and absorption  in the  small intestine  were studied. The intestinal  microflora assessment by identification  of the  bacterial  overgrowth syndrome  in the  small intestine  by respiratory  tests  with lactulosum  was carried out.  Research of hormones  (gastrin,  insulin, hydrocortisone, thyroxine and thyritropic hormone)  was conducted  by method  of the electrochemiluminescence. Results. 91,3% of patients  had disturbances of various stages hydrolytic-resorbtive process in the small intestine, 64,7% of patients had bacterial overgrowth syndrome in the small intestine. Use as part of complex therapy the enzystal and the riboxin rendered a positive effect in stopping the clinical symptoms of cholelithiasis and general enteral symptoms. In the course of treatment cavitary, membrane digestion and absorption in the small intestine distinctly improved. Reliable depression of the gain of concentration of hydrogenium in the expired air from 30,68±9,89 ppm to 8,79±0,72 ppm in the first 60 minutes of research, the bacterial overgrowth syndrome in the small intestine demonstrating decrease is noted. The positive changes in secretion of hormones promoting restoration of the functional characteristics  of the small intestine are taped. Conclusion. Use the enzystal in combination with the riboxin in treatment of the enteropathy in patients with cholelithiasis is pathogenetic reasonable and clinically effective.